(Neo)Victorian Globalisation and Sino-Indian Relations in Amitav Ghosh’s River of Smoke (2011) - Martín-González, Juan José (My University, 2019)
In light of renewed perspectives on Victorian global politics and international relations, this paper provides a close reading of Amitav Ghosh’s River of Smoke (2011). Set in 1839, this second instalment in the so-called Ibis trilogy portrays the trade of opium in early nineteenth-century Canton (today’s Guangzhou) and the Pearl River, casting a variety of characters into the waterways of Victorian imperial exploits right in the prelude to the First Opium War (1839-1842). The close reading provided in this paper pursues two objectives. Firstly, I analyse Ghosh’s neo-Victorian novel as marked by parallels between its narration of the prelude to the First Opium War as a crux in the history of nineteenth-century global trade and current political conflicts arising out of neo-liberal policies and globalisation, including Western military interventions under gunboat diplomacy. In this sense, I follow Sneha Kar Chaudhuri’s suggestion that the novel presages “twentieth- and twenty-first-century diaspora, globalisation, multiculturalism and their attendant dangers, such as drug-trafficking, continuing economic exploitation, and armed conflict over resources” (Chaudhuri 2011: 142). Secondly, I argue that the novel’s reconstruction of India’s involvement in nineteenth-century opium trade in China provides renewed perspectives on Sino-Indians relations in the Victorian period and today. In particular I argue that River of Smoke reconstructs a nineteenth-century Pan-Asian perspective on Indian Ocean relations by illustrating idioms, relations and spaces which escaped the control and hegemony of Victorian imperialism. Ultimately this paper concludes by suggesting that the novel reveals the continuities of the rhetorics of Free Trade and Victorian imperialism in the ideology of neo-liberalism and globalisation today, revealing the Opium Wars as a conflict which determined to a great extent current West-East relations.
Keywords: Globalización; Amitav Ghosh; River of Smoke; Globalisation; Neo-Victorianism